Secure graphical password based on cued click points using fuzzy logic. Issue 2 (19th December 2020) - Ghiyamipour, Fatemeh
Abstract: Nowadays authentication technology is the most important means to ensure security. Alphanumeric username and password procedure is the most common authentication method. Users typically choose memorable passwords that are easy for attackers to guess, and assigned passwords by the system are difficult for users to remember. We present a graphical password based on cued recall in which is secured from shoulder surfing attack. Also, we propose an image encryption technique using a 2D cat map and edge detection technique in which it uses fuzzy logic inference to detect the edge of images. Then the user password is encrypted before storing it in the database using this method. Experiments illustrate that the proposed method has good performance in usability and security.